Achieving NIR Light-Mediated Tumor-Specific Fenton Reaction-Assisted Oncotherapy by Using Magnetic Nanoclusters - Qin, Shaoyou; Xue, Jinru; Jia, Erna; Ren, Na; Dong, Yongqiang; Zhou, Changyu (Frontiers in Oncology, 2021)
As an emerging strategy for oncotherapy, Fenton chemistry can efficiently improve the conversion from endogenous H2O2 into highly toxic •OH in the whole high-performance therapeutic process. Although promising, the efficiency of Fenton reaction in tumor regions is highly limited by the inefficient delivery of Fenton reagents and the restrictive conditions of tumor microenvironment. One promising strategy against above limitations is to specifically increase the temperature around the tumor regions. In this study, a novel NIR light-mediated tumor-specific nanoplatform based on magnetic iron oxide nanoclusters (MNCs) was rationally designed and well developed for photothermally enhanced Fenton reaction-assisted oncotherapy. MNCs could accumulate into the tumor regions with the help of an external magnet field to enable T2-weighted magnetic resonance (MR) imaging of tumors and MR imaging-guided combined antitumor therapy. Our well-prepared MNCs also revealed excellent photothermal effect upon a NIR light irradiation, promising their further important role as a photothermal therapy (PTT) agent. More importantly, heat induced by the PTT of MNCs could accelerate the release of Fe from MNCs and enhance the efficiency of Fenton reaction under H2O2-enriched acidic tumor microenvironment. Results based on long-term toxicity investigations demonstrated the overall safety of MNCs after intravenous injection. This work therefore introduced a novel nanoplatform based on MNCs that exerted a great antitumor effect via photothermally enhanced tumor-specific Fenton chemistry.